2016
DOI: 10.1007/s00125-016-3983-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation of CD3+ T cells from cord blood of infants exposed to intrauterine growth restriction

Abstract: Aims/hypothesis Intrauterine growth restriction (IUGR) is associated with increased susceptibility to obesity, metabolic syndrome and type 2 diabetes. Although the mechanisms underlying the developmental origins of metabolic disease are poorly understood, evidence suggests that epigenomic alterations play a critical role. We sought to identify changes in DNA methylation patterns that are associated with IUGR in CD3 + T cells purified from umbilical cord blood obtained from male newborns who were appropriate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
2
5
0
1
Order By: Relevance
“…Intrauterine growth restricted (IUGR) males and large for gestational age females had epigenetic dysregulation (48). Other reports show similar DNA hypermethylation in the promoter and enhancer regions of the genome in CD3 (+) T cells of IUGR male infants (49). These may be the biomarkers, which could potentially predict metabolic disorders when these infants grow into adulthood.…”
Section: Sex Differences In Growthsupporting
confidence: 59%
“…Intrauterine growth restricted (IUGR) males and large for gestational age females had epigenetic dysregulation (48). Other reports show similar DNA hypermethylation in the promoter and enhancer regions of the genome in CD3 (+) T cells of IUGR male infants (49). These may be the biomarkers, which could potentially predict metabolic disorders when these infants grow into adulthood.…”
Section: Sex Differences In Growthsupporting
confidence: 59%
“…Differential methylation in PTPRN2 in whole blood has been associated with gestational diabetes [ 74 76 ], with childhood adiposity [ 76 ] as well as childhood obesity [ 77 ]. The differential methylation in PTPRN2 has also been associated with intrauterine condition such as IUGR in blood [ 78 , 79 ] but also in adults who have experienced famine, in utero [ 80 ]. These findings provide strong evidence that loci in the fetal PTPRN2 are likely modifiable with maternal nutrition, and detectable in blood later in life.…”
Section: Discussionmentioning
confidence: 99%
“…134 Individuals prenatally exposed to the Dutch famine of 1944-45 had, six decades later, less DNA methylation of the imprinted insulin growth factor-2 gene compared with their unexposed, same-sex siblings. 135 Clinical studies have reported that the DNA methylation pattern in cells from cord blood 136,137 and placenta 138 between FGR human pregnancies and controls is different, affecting genes involved in metabolism and adipose tissue differentiation. Importantly, the phenotypic effects of epigenetic modifications during development may not manifest until later in life, especially if they affect pathways of genes that modulate responses to environmental challenges, such as a high-fat diet.…”
Section: Expert Reviewsmentioning
confidence: 99%